Raspberry Pi 3 Model B+ Based Endure Redicting Using Web of Things (WoT) (International Journal of Innovative Research in Computer Science & Technology, 2022)
The Web of Things (WoT) is a breakthrough  technology that connects and controls the devices with the  help of Web and make them smart and efficient. We build  an WoT based Temperature and Humidity Sensing System  using Raspberry Pi 3 Model B+. Endure is a vital feature  in customary life, which plays a significant part in many  deeds. Therefore, occasionally we need to know Endure parameter instantly. Raspberry Pi is a miniature standalone  system with multiple functionalities were executed. You  will interface a Digital Temperature and Humidity Sensor  to receive regular updates about the Temperature and  Humidity of a location remotely. The Sensor is connected  to Raspberry Pi 3 Model B+, which you will program to  send the readings to the Cloud Server through web, which  in turn send update to Thing Speak. Thing Speak is an  application platform, where the data is sent to the sever for  live monitoring from anywhere in the world over web.  Email notification to the user at intervals. The project  deals about the Temperature and Humidity values, to read  and monitor the values, using ThingSpeak system via  Raspberry Pi 3 Model B+.
Keywords: Raspberry Pi 3 Model B+; Raspbian OS; Debian Bullseye; Temperature; Humidity; Cloud Server; Thing Speak; DHT11 Sensor; Endure Predicting; Networking; System Etiquette; SSH Etiquette; HTTP; PuTTY; VNC Viewer